KONSENTRASI HbA1c BERHUBUNGAN DENGAN TEKANAN DARAH PADA PASIEN DIABETES MELITUS TIPE 2 - Sarah Margaretha; Magdalena Wartono (Fakultas Kedokteran Universitas Trisakti, 2025)
The incidence of diabetes mellitus continues to increase and affecting many people globally. This disease is identified by high blood glucose levels, with one of the parameters examined being HbA1c. High blood glucose levels can cause complications such as high blood pressure. As proven in 2018, where 37.4% of diabetes mellitus patients experienced high blood pressure. The aim of this study was to assess the relationship between HbA1c levels and blood pressure in patients with type-2 diabetes mellitus. This study was conducted using a cross-sectional approach with 96 subjects. The sampling technique used consecutive non-random sampling. Subject characteristics, HbA1c levels, and blood pressure were obtained from medical records. To determine the relationship between HbA1c levels and blood pressure, the Chi-Square test was used in analysis with a significance limit of p < 0.05. The results showed that most subjects were in the age range of 56–65 years (36.5%), female (52.1%), within Obesity I (31.3%), poor glycemic control based on HbA1c levels (83.3%), and high blood pressure (56.2%). There was a significant relationship between HbA1c levels and blood pressure in patients with type-2 diabetes mellitus (p=0.027). Therefore, periodic evaluation of HbA1c levels in individuals with diabetes mellitus is necessary to prevent the occurrence of hypertension complications.